Awareness and acceptability of herpes zoster vaccination in people living with HIV - Christian Motet; Agnès Libois; Charlotte Martin; Nicolas Dauby (Preventive Medicine Reports)
Objective: The recombinant herpes zoster vaccine is recommended for aging populations to prevent herpes zoster. We aimed to assess awareness of herpes zoster and acceptance of the herpes zoster vaccine acceptance among people living with HIV (PLWH). Methods: We conducted a written survey among PLWH attending an HIV outpatient clinic in Brussels from March 2022 to April 2023. Participation was voluntary. We collected epidemiological data, assessed knowledge of herpes zoster and opinion about herpes zoster vaccine and vaccination in general. We described the surveyed cohort and reported their attitudes toward vaccination. Herpes zoster vaccine acceptance and general vaccine acceptance were defined as two binary outcome variables. We performed binary logistic regression to identify factors associated with vaccine acceptance. Results: A total of 327 patients completed the questionnaire. While 64 % reported being aware of herpes zoster, only one third reported a link between herpes zoster and varicella infection. The majority (77.1 %) declared being in favour of overall vaccination. Willingness to be vaccinated (regardless of vaccine type) was the factor associated with herpes zoster vaccine acceptance. General vaccine acceptance was associated with the belief that vaccination is useful for preventing infectious diseases. Conclusions: Knowledge and awareness about herpes zoster were low among PLWH surveyed. Herpes zoster vaccine acceptance was more related to general attitudes toward vaccination rather than specific knowledge about herpes zoster.